Metode Filsafat Keagamaan Islam - Sholihin, Anwar (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
This paper is a philosophical research that discusses the meaning of religion and its relevance in supporting religious plurality in Indonesia. The meaning of the religion was analyzed based on the thoughts of several philosophers. philosophy related to religious beliefs and traditions will only be appropriate and in line if a follower of religion always demands himself to try to understand and live rationally all teachings, doctrines, faith and religious beliefs. Thus, philosophy is no longer seen as an enemy of religion.  The understanding of the adherents of the religion is based on the truth of the religion he believes in. The truth that is used as a benchmark for the scavengers is based on understanding certain religions. Meanwhile, the religious substance is universal. The truth contained in each religion is actually the same / one. Understanding the relativity of religion as a certain form and at the same time having substantive elements is expected to be able to build an open understanding of religion and constructive inter-religious interaction. For religious philosophy is born and there are several approaches and methods in learning it. Philosophy of religion is the philosophy of religion itself, which is thinking about the basics of religion according to free logic. With this approach and method it can provide a clear concept in philosophizing